FIGURES OF SPEECH IN RANI SIMBOLON’S TOBA BATAK POP SONGS - Lusi Rengsi Ana Hutagalung; Sumarsih Sumarsih (LINGUISTICA, 2013)
ABSTRACT This study deals with the figures of speech in the lyrics of Rani Simbolon’s Toba Batak Pop Songs. The objectives of the study are to describe the types of figures of speech which are used in Rani Simbolon’s Toba Batak Pop Songs, to derive the figures of speech that used in Rani Simbolon’s Toba Batak Pop Songs, to reason the figures of speech as found in the Rani Simbolon’s Toba Batak songs. The research was conducted by descriptive qualitative. Thedata are the lyrics of Rani Simbolon’s Toba Batak Pop songs, the data were collected from 10 songs that has figures of speech.This data were analyzed by identifying and classifying the figures of speech displaying the result in a table. Then these figures of spech are described in details. The analysis found that there are four types of figures of speech which used; they are Hyperbole 48,2% , Personification 29,6 %, Simile 14,8 %,and Metaphor 7,4 %. The most frequent type of figures of speech used in the lyrics of Rani Simbolon’s Toba Batak Pop Songs isHyperbole. Keyword:Literature, Figures of speech, Song